Gender-Based Mathematics Anxiety: Strategies for Teachers to Foster Confidence and Inclusion - Beteno, Septrisno; Hastomo, Agung; Hadi, Najmul (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to examine how teachers address students' mathematics anxiety from a gender perspective at a public high school in Mataram. Employing a qualitative approach with a case study design, this research involves in-depth interviews and document analysis. The participants include mathematics teachers and students who experience varying levels of mathematics anxiety. The research process encompasses participant selection, instrument preparation and validation, data collection through interviews regarding teachers' strategies for managing mathematics anxiety, data analysis, triangulation, and interpretation. The findings reveal that teachers implement several key strategies, including fostering a supportive and inclusive learning environment, utilizing collaborative and differentiated instruction, integrating technology, and providing gender-sensitive feedback. These strategies have proven effective in reducing students' anxiety and increasing their confidence in mathematics learning. The study highlights the crucial role of teachers in mitigating mathematics anxiety and promoting equitable learning experiences. Future research could explore the impact of these strategies in different educational settings and examine additional factors influencing mathematics anxiety from a broader perspective.